Vital Tooth Bleaching: A Case Report - Maiti, Niladri; Das, Utpal Kumar (The Journal of Dentists, 2014)
A dazzling white smile has been a symbol of beauty, health and vitality for hundreds of years. Discolouration, especially when the front teeth are affected, means a significant disturbance of aesthetics and can decrease a patient’s self esteem. Public demand for aesthetic dentistry, including tooth whitening, has increased in recent years. Compared with restorative treatment modalities, whitening, also referred to as bleaching, is the most conservative treatment for discolored teeth. This public demand for a whiter smile and improved aesthetics has made tooth whitening a popular and often requested dental procedure, since it offers a conservative treatment option for discolored teeth. Whitening often enhances the treatment and encourages patients to seek further aesthetic treatment. Dental bleaching offers a conservative, simplified, and low cost approach to change the color of discoloured teeth. Current bleaching techniques include a dentist-prescribed in-office technique, an at-home applied technique, or a combination of both. The pigments oxidation is responsible for tooth bleaching and can be carried out with two different products; carbamide peroxide and hydrogen peroxide. This case report reflects the remarkable change of tooth color by in-office bleaching.